Analysis and Countermeasures of related factors between mental health and physical exercise of Law College Students - Sheng Zeng; Lin Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The goal of this study is to investigate and test if physical exercise affects the mental health of law students. is study aim. The current study used a quantitative research approach. A questionnaire survey is carried out to collect data from respondents. Furthermore, a planned physical exercise in the experimental and control groups is used. Finally, data analysis is carried out by using a statistical tool. There was no significant difference in the level of SCL-90 between the two groups (P > 0.05). There was no significant difference in mental health between the experimental group and the control group, which met the requirements of the experiment. Through T-analysis of the data before and after the investigation, there were significant differences in somatization, obsessive-compulsive symptoms, and interpersonal sensitivity in the experimental group (P ≤ 0.05), and there were very significant differences in anxiety factors (P ≤ 0.01). Physical exercise intervention can significantly alleviate the bad mood of college students. Physical exercise is conducive to improving college students' intelligence level and reducing the learning pressure. Different sports have different effects on the psychological factors of college students; The overall impact of personal sports on psychological conditions is better than that of collective sports. Collective sports can enhance people's aggressive psychology, but individual sports individual sports cannot replace the advantages of collective sports on interpersonal relationship cannot replace the advantages of collective sports on interpersonal relationship.